Multimodal Discourse Analysis on Educational Vlogs - Altamera, Gloryjean; Cubelo, Ramil (International Journal of Language and Literary Studies, 2025)
This qualitative study aimed to examine the construction and communication of meaning of the educational vlogs through their audio and verbal elements and how multimodal features worked together. There were fifty-two (52) educational vlogs from YouTube that served as the corpus of the study and were analyzed through Multimodal Discourse Analysis. The audio elements found were the controlled upbeat background music and insertion of sound effects, and the verbal elements were directive, phatic, informative, and expressive language functions. Finally, it revealed that lack of interest is the main educational issue raised by the vloggers in the corpora. Nevertheless, through the use of multimodality in teaching, this allows teachers and students to obtain information through multiple channels and jointly construct the meaning.